Developing Writing Skills in English Using Content-Specific Computer-Generated Feedback with EssayCritic - Irina Engeness; Anders Mørch (Universitetsforlaget, 2016)
This paper presents a study of Norwegian Upper Secondary School students' writing process in English with: 1) feedback from an essay critiquing system (EssayCritic) (target class) and 2) feedback from collaborating peers (comparison class). The students in both classes significantly improved their grades. In the target class, the feedback from EssayCritic gave content-specific cues and the students included more ideas in their essays than the students in the comparison class who struggled when giving feedback to each other.